Lithium ion battery diaphragm and preparation method thereof
By setting up an antioxidant layer of sustained release antioxidant on the lithium-ion battery separator to capture the oxygen free radicals in the electrolyte, the problem of defiling of the electrode sheet caused by oxygen free radicals is solved, and the cycle stability and life of the battery are significantly improved.
Patent Information
- Application Number
- CN202411607111.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The presence of oxygen radicals in lithium-ion batteries causes the electrode sheet to be defiled, which in turn affects the cycle life and stability of the battery.
An antioxidant layer with sustained-release antioxidant is provided on the separator of the lithium-ion battery, and the antioxidant of terbutyl hydroquinone, dibutyl hydroxytoluene, and tea polyphenol are loaded on the sustained-release carrier polymethyl methacrylate by loading the sustained-release carrier by terbutyl hydroquinone, dibutyl hydroxytoluene, and tea polyphenol antioxidant on the sustained-release carrier polymethyl methacrylate Or on polyvinylidene fluoride, capture the oxygen radicals in the electrolyte and block its reaction with the electrolyte or binder.
It effectively improves the cycle stability and life of lithium-ion batteries, reduces the phenomenon of defiling of the electrode sheet caused by oxygen free radicals, and improves the long-term stability of the battery.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery separator and a preparation method thereof. Background Art
[0002] With the continuous development of my country's new energy industry, energy storage batteries, as an important part of the industrial chain, have increasingly stringent performance requirements. With the continuous development of photovoltaic technology, its design service life has reached 20-25 years, and correspondingly, higher cycle life requirements have been put forward for its supporting energy storage power stations. In order to ensure the goal of equal life of photovoltaic and energy storage, the current service life of energy storage batteries needs to meet at least 15,000 weeks.
[0003] At present, energy storage batteries are mainly based on lithium iron phosphate systems, and the general service life of lithium iron phosphate systems is 10,000 to 12,000 weeks. In order to further improve the service life of lithium iron phosphate system batteries, various battery suppliers are considering the use of lithium replenishment technology. Among them, the fastest-promoting and most mature is the positive electrode lithium replenishment technology, that is, the positive electrode lithium replenisher releases additional lithium during the first charging process and stores it in the negative electrode to replenish the gradual loss of active lithium in the later stage of the cycle, so as to achieve the effect of improving the cycle life. However, the current mainstream positive electrode lithium replenishers, including Li2O, Li2O2, Li2C2O4, Li2C4O4, Li5FeO4, Li6CoO4, Li2NiO2, etc., will decompose during the first charge or form more oxygen free radicals during the later cycle. These oxygen free radicals will cause the oxidation of the binder, which will lead to the delamination of the pole piece, and ultimately lead to rapid deterioration of battery performance. Summary of the invention
[0004] In order to solve the technical problem of pole piece demoulding caused by oxygen free radicals, the present invention provides a lithium ion battery separator and a preparation method thereof. The present invention loads tertiary butylhydroquinone, dibutylhydroxytoluene, and tea polyphenol antioxidants on a slow-release carrier polymethyl methacrylate or / and polyvinylidene fluoride, and coats them on the surface of the separator substrate, and an antioxidant layer with a slow-release antioxidant that captures oxygen free radicals in the electrolyte is arranged on the separator, thereby achieving a long-term stable effect of the battery.
[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a lithium-ion battery separator, comprising a separator substrate and an antioxidant layer disposed on the surface of the separator substrate, wherein the antioxidant layer comprises an antioxidant and a sustained-release carrier, wherein the antioxidant is selected from one or more of tertiary butylhydroquinone (TBHQ), butylated hydroxytoluene (BHT), and tea polyphenols (TP), and the sustained-release carrier is polymethyl methacrylate and / or polyvinylidene fluoride.
[0006] At present, lithium-ion batteries have the problem of excessive oxygen free radical content in the electrolyte, especially lithium-ion batteries containing positive electrode lithium supplements. Oxygen free radicals will react with the electrolyte or binder to destroy the stability of the battery. Therefore, the present invention has carried out a series of experiments and studies on the problem of excessive oxygen free radical content in current lithium-ion batteries.
[0007] The inventors have found that in a battery containing a positive electrode lithium supplement, the positive electrode lithium supplement will decompose to form a large number of oxygen free radicals released into the electrolyte during the first charge, and the residue of the lithium supplement will also cause some oxygen free radicals to continue to form during the later cycle. Therefore, the present invention takes into account the large-scale generation of oxygen free radicals during the first charging period and their continued generation in the later period, and provides a battery separator, which realizes the long-term stability of the battery by arranging an antioxidant layer with a slow-release antioxidant on the surface of the separator substrate to capture oxygen free radicals in the electrolyte. The slow-release effect of the antioxidant layer of the present invention is mainly achieved by loading tert-butylhydroquinone, dibutylhydroxytoluene, and tea polyphenol antioxidants on the slow-release carrier polymethyl methacrylate or / and polyvinylidene fluoride. The antioxidant on the antioxidant layer of the present invention can capture oxygen free radicals in contact with the antioxidant layer, and can slowly release the antioxidant into the electrolyte, capture oxygen free radicals in the electrolyte within a large spatial range and a long time range, block the reaction of oxygen free radicals with the electrolyte or the binder, and greatly improve the stability of the battery.
[0008] As a preferred embodiment of the above-mentioned diaphragm, the mass ratio of the antioxidant to the sustained-release carrier is 0.5~4:1.
[0009] The slow-release effect of the antioxidant layer of the present invention is related to the mass ratio of the antioxidant to the slow-release carrier, and the mass ratio of the antioxidant to the slow-release carrier is preferably 0.5 to 4: 1. If the mass of the antioxidant is too small, it cannot take into account the role of capturing oxygen free radicals in a larger range in the battery, nor the role of capturing oxygen free radicals in the later charge and discharge process, so the battery stability is low; if the mass of the antioxidant is too large, there will be a problem that the antioxidant adheres to the electrode to generate additional redox reactions.
[0010] More preferably, the mass ratio of antioxidant to sustained-release carrier is 1.5-3:1.
[0011] As a preferred embodiment of the above-mentioned diaphragm, the diaphragm substrate is one of a PP diaphragm, a PE diaphragm, a composite diaphragm of PP and PE, a PP diaphragm including an inorganic ceramic coating, a PE diaphragm including an inorganic ceramic coating, and a composite diaphragm of PP and PE including an inorganic ceramic coating. The inorganic ceramic coating may be a conventional inorganic ceramic coating for lithium-ion battery diaphragms on the market, such as an alumina coating.
[0012] As a preferred embodiment of the above-mentioned diaphragm, the thickness of the anti-oxidation layer is 1-5 μm.
[0013] The sustained release effect of the antioxidant layer of the present invention is related to the thickness of the antioxidant layer, and the thickness of the antioxidant layer is 1 to 5 μm. If the thickness of the antioxidant layer is too small, it cannot take into account the role of capturing oxygen free radicals in a larger range in the battery, nor can it take into account the role of capturing oxygen free radicals in the later charging and discharging process. Therefore, the battery stability is low; if the thickness of the antioxidant layer is too large, the bonding effect with the diaphragm substrate is poor, and it will fall off directly in the later charging and discharging process. The local antioxidant concentration is too high, and then the local concentration is too low, which will lead to the problem of interface deterioration, and ultimately lead to a decrease in battery performance. At the same time, the thickness of the antioxidant layer is too large, which will take up more battery space, resulting in low battery energy density, which will also lead to a decrease in battery performance.
[0014] More preferably, the thickness of the anti-oxidation layer is 1.5-2.5 μm.
[0015] In a second aspect, the present invention provides a method for preparing a lithium ion battery separator, comprising the following steps: Step S1: mixing the sustained-release carrier with the solvent and dispersing at high speed to obtain a sustained-release carrier liquid; Step S2: adding an antioxidant to the sustained-release carrier liquid, mixing evenly, and obtaining an antioxidant layer slurry; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying; in: The sustained-release carrier is polymethyl methacrylate and / or polyvinylidene fluoride; The antioxidant is selected from one or more of tert-butylhydroquinone, dibutylhydroxytoluene and tea polyphenols.
[0016] For the above-mentioned diaphragm with slow-release antioxidant function, the present invention is prepared by the above-mentioned steps S1 to S3. First, the slow-release carrier polymethyl methacrylate or / and polyvinylidene fluoride are mixed with a solvent, and dispersed evenly under high-speed dispersion to form a slow-release carrier in the form of a slurry, and then tertiary butylhydroquinone, dibutylhydroxytoluene, and tea polyphenols are added to the slow-release carrier to obtain an antioxidant layer slurry, and the slurry is coated on the surface of the diaphragm substrate, dried, and the solvent is removed, and the antioxidant is successfully loaded in the slow-release carrier, and an antioxidant layer loaded with the antioxidant is formed on the surface of the diaphragm substrate.
[0017] The solvent may be a common organic solvent, preferably one that can form a slurry with the sustained-release carrier, such as N-methylpyrrolidone (NMP), dimethylformamide (DMF), dichloromethane (DCM), etc. The amount of solvent added is based on the mass of the sustained-release carrier, and the mass ratio of the solvent to the sustained-release carrier is preferably 4 to 20:1.
[0018] As a preferred embodiment of the above preparation method, in step S1, the linear speed of high-speed dispersion is 15-25 m / s and the time is 100-140 min.
[0019] The linear speed of the high-speed dispersion of the sustained-release carrier and the solvent is preferably 15-25 m / s. At this linear speed, the sustained-release carrier can be dispersed without micelles. The presence of micelles will cause uneven mixing of the antioxidant and the sustained-release carrier, affecting the sustained-release effect. Too high or too low a dispersion speed is not conducive to uniform dispersion of the sustained-release carrier in the solvent, and will lead to the appearance of micelles or foams.
[0020] As a preferred embodiment of the above preparation method, in step S3, the drying temperature is 80-100°C.
[0021] The drying effect can remove the solvent and promote the loading of the antioxidant, and the drying temperature is preferably 80-100° C. The drying temperature should not be too high, as too high a temperature may destroy the molecular structure of the antioxidant and deteriorate the antioxidant effect.
[0022] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator of the lithium-ion battery adopts the lithium-ion battery separator provided by the present invention.
[0023] The lithium ion battery provided by the present invention using the diaphragm provided by the present invention has excellent cycle stability and cycle life.
[0024] Compared with the prior art, the present invention has the following technical effects: The present invention takes into account the large-scale generation of oxygen free radicals during the first charging period and their continued generation in the later period, and provides a battery separator. By setting an antioxidant layer with a slow-release antioxidant on the surface of the separator substrate to capture oxygen free radicals in the electrolyte, the long-term stability of the battery is achieved. The slow-release effect of the antioxidant layer of the present invention is achieved by loading tertiary butylhydroquinone, dibutylhydroxytoluene, and tea polyphenol antioxidants on a slow-release carrier polymethyl methacrylate or / and polyvinylidene fluoride. The antioxidant on the antioxidant layer of the present invention can capture oxygen free radicals in contact with the antioxidant layer, and can slowly release the antioxidant into the electrolyte, capturing oxygen free radicals in the electrolyte within a large spatial range and a long time range, blocking the reaction of oxygen free radicals with the electrolyte or the binder, so that the battery stability is greatly improved. The antioxidant layer of the present invention can be set on the surface of the common separator currently on the market to achieve the effect of slow-release antioxidants to capture oxygen free radicals in the electrolyte, improve battery stability, and further improve the service life of current energy storage batteries. The separator provided by the present invention has a wide range of applications. DETAILED DESCRIPTION
[0025] Taking into account the problems of large-scale generation of oxygen free radicals during the first charging period and their continued generation in the later period, the present invention provides a battery separator, which is coated on the surface of the separator substrate by loading tert-butylhydroquinone, dibutylhydroxytoluene, and tea polyphenol antioxidants on a slow-release carrier polymethyl methacrylate or / and polyvinylidene fluoride, so that an antioxidant layer with a slow-release antioxidant to capture oxygen free radicals in the electrolyte is provided on the separator, thereby achieving a long-term stable effect of the battery. The separator substrate can be a conventional separator for lithium-ion batteries on the market, for example, a PP (polypropylene) separator, a PE (polyethylene) separator, a composite separator of PP and PE, a PP separator containing an inorganic ceramic coating, a PE separator containing an inorganic ceramic coating, a composite separator of PP and PE containing an inorganic ceramic coating, etc.
[0026] The present invention is further described with a PE diaphragm containing an inorganic ceramic coating as the diaphragm substrate. A person skilled in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by a person skilled in the art without making creative work should fall within the scope of protection of the present invention.
[0027] The diaphragm substrate used in the following examples was purchased from Xingyuan Material Technology Co., Ltd., with specifications of 1.5 μm PVDF layer + 7 μm PE + 2 μm ceramic layer + 1.5 μm PVDF layer.
[0028] Example 1 A lithium ion battery separator is provided, which is prepared according to the following method: Step S1: mixing a sustained-release carrier polymethyl methacrylate and NMP in a mass ratio of 1:8, and dispersing at a linear speed of 20 m / s for 120 min to obtain a micelle-free sustained-release carrier liquid; Step S2: adding the antioxidant tea polyphenols to the sustained-release carrier liquid, stirring evenly at a linear speed of 15 m / s to obtain an antioxidant layer slurry; wherein the mass ratio of the antioxidant to the sustained-release carrier is 2:1; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying it at 85° C. After testing, a 2.0 μm anti-oxidation layer was formed on the surface of the diaphragm substrate.
[0029] Example 2 A lithium ion battery separator is provided, which is prepared according to the following method: Step S1: mixing a sustained-release carrier polymethyl methacrylate and NMP in a mass ratio of 1:8, and dispersing at a linear speed of 20 m / s for 120 min to obtain a micelle-free sustained-release carrier liquid; Step S2: adding the antioxidant tert-butylhydroquinone to the sustained-release carrier liquid, stirring evenly at a linear speed of 15 m / s to obtain an antioxidant layer slurry; wherein the mass ratio of the antioxidant to the sustained-release carrier is 2:1; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying it at 85° C. After testing, a 2.0 μm anti-oxidation layer was formed on the surface of the diaphragm substrate.
[0030] Example 3 A lithium ion battery separator is provided, which is prepared according to the following method: Step S1: mixing a sustained-release carrier polymethyl methacrylate and NMP in a mass ratio of 1:8, and dispersing at a linear speed of 20 m / s for 120 min to obtain a micelle-free sustained-release carrier solution; Step S2: adding antioxidant butylated hydroxytoluene to the sustained-release carrier liquid, stirring evenly at a linear speed of 15 m / s to obtain an antioxidant layer slurry; wherein the mass ratio of the antioxidant to the sustained-release carrier is 2:1; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying it at 85° C. After testing, a 2.0 μm anti-oxidation layer was formed on the surface of the diaphragm substrate.
[0031] Example 4 A lithium ion battery separator is provided, which is prepared according to the following method: Step S1: mixing the sustained-release carrier polyvinylidene fluoride and NMP in a mass ratio of 1:8, and dispersing at a linear speed of 20 m / s for 120 min to obtain a micelle-free sustained-release carrier solution; Step S2: adding the antioxidant tea polyphenols to the sustained-release carrier liquid, stirring evenly at a linear speed of 15 m / s to obtain an antioxidant layer slurry; wherein the mass ratio of the antioxidant to the sustained-release carrier is 2:1; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying it at 85° C. After testing, a 2.0 μm anti-oxidation layer was formed on the surface of the diaphragm substrate.
[0032] Example 5 A lithium ion battery separator is provided, which is prepared according to the following method: Step S1: mixing the sustained-release carrier polymethyl methacrylate and NMP in a mass ratio of 1:4, and dispersing at a linear speed of 25 m / s for 100 min to obtain a micelle-free sustained-release carrier solution; Step S2: adding the antioxidant tea polyphenols to the sustained-release carrier liquid, stirring evenly at a linear speed of 15 m / s to obtain an antioxidant layer slurry; wherein the mass ratio of the antioxidant to the sustained-release carrier is 3:1; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying it at 90° C. After testing, an anti-oxidation layer of 1.5 μm was formed on the surface of the diaphragm substrate.
[0033] Example 6 A lithium ion battery separator is provided, which is prepared according to the following method: Step S1: mixing the sustained-release carrier polymethyl methacrylate and NMP in a mass ratio of 1:20, and dispersing at a linear speed of 15 m / s for 140 min to obtain a micelle-free sustained-release carrier solution; Step S2: adding the antioxidant tea polyphenols to the sustained-release carrier liquid, stirring evenly at a linear speed of 15 m / s to obtain an antioxidant layer slurry; wherein the mass ratio of the antioxidant to the sustained-release carrier is 1.5:1; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying it at 90° C. After testing, a 2.5 μm anti-oxidation layer was formed on the surface of the diaphragm substrate.
[0034] Example 7 A lithium ion battery separator is provided, which is prepared according to the following method: Step S1: mixing a sustained-release carrier polymethyl methacrylate and NMP in a mass ratio of 1:10, and dispersing at a linear speed of 25 m / s for 120 min to obtain a micelle-free sustained-release carrier solution; Step S2: adding the antioxidant tea polyphenols to the sustained-release carrier liquid, stirring evenly at a linear speed of 15 m / s to obtain an antioxidant layer slurry; wherein the mass ratio of the antioxidant to the sustained-release carrier is 0.5:1; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying it at 90° C. After testing, a 5.0 μm anti-oxidation layer was formed on the surface of the diaphragm substrate.
[0035] Example 8 A lithium ion battery separator is provided, which is prepared according to the following method: Step S1: mixing the sustained-release carrier polymethyl methacrylate and NMP in a mass ratio of 1:10, and dispersing at a linear speed of 15 m / s for 120 min to obtain a micelle-free sustained-release carrier solution; Step S2: adding antioxidant tea polyphenols to the sustained-release carrier liquid, stirring at a linear speed of 15 m / s to obtain an antioxidant layer slurry; wherein the mass ratio of the antioxidant to the sustained-release carrier is 4:1; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying it at 90° C. After testing, a 1.0 μm anti-oxidation layer was formed on the surface of the diaphragm substrate.
[0036] Comparative Example 1 A lithium ion battery separator is provided, which is different from Example 1 in that no anti-oxidation layer is provided and the rest is the same as Example 1, that is, the separator substrate is the same as Example 1, but no operation is performed.
[0037] Comparative Example 2 A lithium-ion battery separator is provided, which is different from Example 1 in that the antioxidant tea polyphenol is replaced by another different type of antioxidant hindered amine antioxidant Chiguard 4050 (chemical name: N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-N,N'-dialdehyde hexanediamine). The rest is the same as Example 1.
[0038] Comparative Example 3 A lithium-ion battery separator is provided, which is different from Example 1 in that the antioxidant tea polyphenol is replaced with other different types of antioxidant ascorbic acid (insoluble in electrolyte). Other aspects are the same as Example 1.
[0039] Comparative Example 4 A lithium-ion battery separator is provided, which is different from Example 1 in that the antioxidant tea polyphenol is replaced with other conventional antioxidant butylated hydroxyanisole (soluble in electrolyte) of the same type. The rest is the same as Example 1.
[0040] Comparative Example 5 A lithium ion battery separator is provided, which is different from Example 1 in that the thickness of the anti-oxidation layer is 0.5 μm and the rest is the same as Example 1.
[0041] Comparative Example 6 A lithium ion battery separator is provided, which is different from Example 1 in that the thickness of the anti-oxidation layer is 6.0 μm and the rest is the same as Example 1.
[0042] Comparative Example 7 A lithium ion battery separator is provided, which is different from Example 1 in that the linear speed of high-speed dispersion is 10 m / s. The rest is the same as Example 1.
[0043] Comparative Example 8 A lithium ion battery separator is provided, which is different from Example 1 in that the linear speed of high-speed dispersion is 30 m / s and the rest is the same as Example 1.
[0044] Performance Characterization The battery separators provided in the embodiments and comparative examples were used to prepare lithium-ion batteries, and the cycle performance was tested. The performance of the battery separators provided in the embodiments and comparative examples was characterized by characterizing the cycle stability of the lithium-ion batteries, and the results are shown in Table 1. Among them, the powder loss of the fully charged negative electrode is usually caused by the cracking or loosening of the binder of the negative electrode material during the charge and discharge cycle, and the cracking or loosening of the binder is caused by the oxidation of oxygen free radicals, which can characterize the influence of oxygen free radicals on the stability of the battery.
[0045] The method for preparing a lithium ion battery is: (1) Preparation of positive electrode sheet: The formula is LFP: Li6CoO4: SP: PVDF = 94.5%: 2.5%: 1.0%: 2.0% (mass ratio). Mix the materials according to the formula to prepare a mixed slurry, which is coated on an aluminum foil with a thickness of 13 μm. The coating surface density is 340 g / m 2 ; Then roll the coated and dried pole piece to a thickness of 150um; die-cut into small pieces; (2) Preparation of negative electrode sheet: The formula is graphite: SP: CMC: SBR = 96%: 1.0%: 1.3%: 1.7% (mass ratio). Mix the materials according to the formula to prepare a mixed slurry, which is coated on a copper foil with a thickness of 6 μm. The coating surface density is 170 g / m 2 ; Then roll the coated and dried pole piece to a thickness of 110um; die-cut into small pieces; (3) The positive electrode sheet, the negative electrode sheet, and the diaphragm are stacked to form a bare cell, which is placed in an aluminum-plastic film, and then vacuum-baked at 95°C to remove moisture, and then the electrolyte is injected to seal the cell to obtain a lithium-ion battery, which is then left to stand, formed, degassed, sealed, and volume separated. The electrolyte composition is: ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:3:4 to obtain a mixed solution of an organic solvent, and then fully dried LiPF6 is dissolved in the mixed solution of the organic solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0046] The test method for the powder loss of the fully charged negative electrode is: After capacity division, the battery cells are first disassembled with full charge to observe the powder loss of the negative electrode.
[0047] The test method for the capacity retention rate after 500 cycles is: Empty the battery, and then charge and discharge it according to the following process: Each complete charge and discharge process is recorded as 1 week, with the capacity of the first week as the initial capacity C1, and the capacity of the 500th week as C500. The capacity retention rate after 500 cycles is η1 = C500 / C1. Among them: the battery emptying process is: 1C constant current discharge to the lower limit voltage of 2.5V; the charge and discharge process is: 1C constant current constant voltage charging, upper limit voltage 3.65V, cut-off current 0.05C; stand for 10min; 1C constant current discharge to the lower limit voltage 2.5V; stand for 10min.
[0048] The test method for the increase ratio of internal resistance after 500 cycles is: Using a conventional voltage internal resistance tester, the AC internal resistance of the battery in the first week of the test cycle is R1; the AC internal resistance of the battery in the 500th week of the cycle is recorded as R500; the internal resistance growth rate of the battery after 500 cycles is η2 = R500 / R1.
[0049] Table 1 Group Fully charged negative electrode powder loss Capacity retention rate after 500 cycles Internal resistance growth ratio after 500 cycles Example 1 No powder loss 99.0% 4.1% Example 2 No powder loss 96.9% 6.8% Example 3 No powder loss 96.8% 6.2% Example 4 No powder loss 97.0% 5.7% Example 5 No powder loss 97.5% 4.5% Example 6 No powder loss 97.3% 5.0% Example 7 Slightly powdery edges 90.1% 8.1% Example 8 No powder loss 93.1% 7.2% Comparative Example 1 Large area of powder loss 84.4% 33.7% Comparative Example 2 Large area of powder loss 88.1% 25.4% Comparative Example 3 Large area of powder loss 86.4% 28.9% Comparative Example 4 Slightly powdery edges 88.5% 25.0% Comparative Example 5 Slightly powdery edges 86.0% 28.7% Comparative Example 6 No powder loss 87.3% 24.2% Comparative Example 7 Edge powder loss 86.6% 28.9% Comparative Example 8 Edge powder loss 87.0% 24.7% From Table 1, we can see that: (1) The present invention loads tert-butylhydroquinone, dibutylhydroxytoluene, and tea polyphenol antioxidants on a slow-release carrier polymethyl methacrylate or polyvinylidene fluoride, and coats the resultant on the surface of the diaphragm substrate, thereby providing an antioxidant layer on the diaphragm that has a slow-release antioxidant that can capture oxygen free radicals in the electrolyte. This can achieve long-term stability of the battery, and the capacity retention rate can reach 99.0% after 500 cycles.
[0050] (2) By comparing Comparative Examples 2 to 4 with Example 1, it can be seen that the selection of antioxidants has an effect on the slow-release antioxidant effect of the antioxidant layer of the present invention.
[0051] (3) By comparing Comparative Examples 5 to 6 with Example 1, it can be seen that the thickness of the antioxidant layer will affect the slow-release antioxidant effect. It can be seen that the thickness of the antioxidant layer is preferably 1 to 5 μm. If the thickness of the antioxidant layer is too small, it cannot take into account the role of capturing oxygen free radicals in a larger range in the battery, nor can it take into account the role of capturing oxygen free radicals in the later charging and discharging process. Therefore, the battery stability is low; if the thickness of the antioxidant layer is too large, the bonding effect with the diaphragm substrate is poor, and it will directly fall off during the later charging and discharging process. The local antioxidant concentration is too high, and then the local concentration is too low, which will lead to the problem of interface deterioration, and ultimately lead to a decrease in battery performance; at the same time, the thickness of the antioxidant layer is too large, it will occupy more battery space, resulting in low battery energy density, which will also lead to a decrease in battery performance.
[0052] (4) By comparing Comparative Examples 7 to 8 with Example 1, it can be seen that the dispersion speed during the preparation of the slow-release carrier liquid affects the slow-release antioxidant effect. It can be seen that the linear speed of the high-speed dispersion of the slow-release carrier and the solvent is preferably 15-25 m / s. Too high or too low a dispersion speed is not conducive to the uniform dispersion of the slow-release carrier in the solvent, which will lead to the appearance of micelles or foams, which is not conducive to the loading of the antioxidant and causes uneven loading, affecting the slow-release effect, and ultimately, the battery stability is low.
[0053] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0054] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A lithium ion battery separator, characterized in that: It includes a diaphragm substrate and an antioxidant layer arranged on the surface of the diaphragm substrate, the antioxidant layer includes an antioxidant and a sustained-release carrier, the antioxidant is selected from one or more of tertiary butylhydroquinone, dibutylhydroxytoluene, and tea polyphenols, and the sustained-release carrier is polymethyl methacrylate and / or polyvinylidene fluoride.
2. A lithium ion battery separator according to claim 1, characterized in that: The mass ratio of antioxidant to sustained-release carrier is 0.5~4:
1.
3. A lithium ion battery separator according to claim 2, characterized in that: The mass ratio of antioxidant to sustained-release carrier is 1.5~3:
1.
4. A lithium ion battery separator according to claim 1, characterized in that: The membrane substrate is one of a PP membrane, a PE membrane, a composite membrane of PP and PE, a PP membrane including an inorganic ceramic coating, a PE membrane including an inorganic ceramic coating, and a composite membrane of PP and PE including an inorganic ceramic coating.
5. A lithium ion battery separator according to claim 1, characterized in that: The thickness of the anti-oxidation layer is 1-5 μm.
6. A lithium ion battery separator according to claim 5, characterized in that: The thickness of the anti-oxidation layer is 1.5-2.5 μm.
7. A method for preparing a lithium ion battery separator, characterized in that: The following steps are involved: Step S1: mixing the sustained-release carrier with the solvent and dispersing at high speed to obtain a sustained-release carrier liquid; Step S2: adding an antioxidant to the sustained-release carrier liquid, mixing evenly, and obtaining an antioxidant layer slurry; Step S3: coating the anti-oxidation layer slurry on the surface of the diaphragm substrate and drying; in: The sustained-release carrier is polymethyl methacrylate and / or polyvinylidene fluoride; The antioxidant is selected from one or more of tert-butylhydroquinone, dibutylhydroxytoluene and tea polyphenols.
8. The preparation method according to claim 7, characterized in that: In step S1, the linear speed of high-speed dispersion is 15-25 m / s and the time is 100-140 min.
9. The preparation method according to claim 7, characterized in that: In step S3, the drying temperature is 80-100°C.
10. A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The separator is a lithium-ion battery separator as claimed in any one of claims 1 to 6.
Citation Information
Patent Citations
Lithium ion battery separator and preparation method thereof
CN106252563A
Anti-oxidation high-puncture-strength dry diaphragm and preparation method and application thereof
CN110165129A
Polymer ceramic diaphragm with high cycle performance and preparation method thereof
CN115566358A
Lithium ion electrolyte for improving circulation and battery
CN118156598A
Separator of lithium secondary battery and the lithium secondary battery with the same
KR1020160092862A